2019
DOI: 10.1007/s40544-019-0287-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular behaviors in thin film lubrication—Part one: Film formation for different polarities of molecules

Abstract: There are three unsolved problems in thin film lubrication (TFL) since it was proposed 20 years ago, i.e., the determination of the type of molecules that can enter the contact region efficiently during sliding, the orientation of molecules in the contact region, and the effect of solid surfaces on the liquid molecular orientation in TFL. In order to answer the first two questions, an in situ measurement system comprising a self-designed Raman microscopy and relative optical interference intensity (ROII) syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…11. Their results indicate that the orientation of liquid molecules in central region of the gap is guided by the shear direction [109] and that of polar molecules near the solid surface (Ag) is guided by solid material [108]. The TFL model with a nanosandwich structure consisting of an adsorbed layer, an ordered-molecule layer, and a fluid layer has been verified.…”
Section: Oil-based Lubricationmentioning
confidence: 91%
See 1 more Smart Citation
“…11. Their results indicate that the orientation of liquid molecules in central region of the gap is guided by the shear direction [109] and that of polar molecules near the solid surface (Ag) is guided by solid material [108]. The TFL model with a nanosandwich structure consisting of an adsorbed layer, an ordered-molecule layer, and a fluid layer has been verified.…”
Section: Oil-based Lubricationmentioning
confidence: 91%
“…The TFL molecular model proposed in 1996 had not been validated experimentally so far. However, there has been a major breakthrough in 2019 [108,109]. Gao et al [108] developed a method based on surfaceenhanced Raman spectroscopy which can show both the packing and orientation of liquid molecules in the TFL regime as shown in Fig.…”
Section: Oil-based Lubricationmentioning
confidence: 99%
“…For instance, an enrichment effect in the Hertz contact region was observed when dispersing polar additive molecules into a nonpolar base oil, which can be explained by the interaction between polar additive molecules and the steel surface. However, there was no enrichment effect for nonpolar molecules dispersed into the nonpolar base oil and polar molecules dispersed into polar base oil [148]. Nanolubricant additives with low chemical activity such as copper, silver, and graphene always form a physical adsorption tribofilm.…”
Section: Formation Of Tribofilmmentioning
confidence: 99%
“…Owing to their high polarity and molecular orientation, liquid crystals exhibit attractive tribological properties both as base oil and as lubricant additives [17] . Luo et al [18][19][20] found that when a nematic liquid crystal 5CB (4-n-pentyl-4'-cyanobiphenyl) was added to hexadecane, the lubricant film became thicker but the coefficient of friction (COF) was even significantly reduced. This actually contradictory behavior was explained by the thin film lubrication theory where molecules attach themselves to the surface and the shear induces a specific molecular orientation.…”
Section: Introductionmentioning
confidence: 99%